Long-term growth in Malaysia: An application of endogenous neoclassical growth model - Rahmah Ismail (Penerbit Universiti Kebangsaan Malaysia, 1999)
The neoclassical growth model shows that the growth of output is not determined by the saving rate, but it is constrained by the rate of growth of the labour force. Therefore, in order to increase the output growth higher than that of the labour productivity must be improved. This article attempts to test this model in the Malaysia's growth experience using data of 1970-1996. The finding from this study shows that the Malaysia's experience is in accordance with the neoclassical growth model postulation that is saving rate does not significantly determine the rate of output growth. Instead, it is determined by the growth of export, population and government expenditure on education. However, level of saving is crucial in determining level of output